Where Sounds Occur Matters: Context Effects Influence Processing of Salient Vocalisations - Atiqah Azhari; Paola Rigo; Marc H. Bornstein; Gianluca Esposito (Brain Sciences, 2020)
The social context in which a salient human vocalisation is heard shapes the affective information it conveys. However, few studies have investigated how visual contextual cues lead to differential processing of such vocalisations. The prefrontal cortex (PFC) is implicated in processing of contextual information and evaluation of saliency of vocalisations. Using functional Near-Infrared Spectroscopy (fNIRS), we investigated PFC responses of young adults (N = 18) to emotive infant and adult vocalisations while they passively viewed the scenes of two categories of environmental contexts: a domestic environment (DE) and an outdoors environment (OE). Compared to a home setting (DE) which is associated with a fixed mental representation (e.g., expect seeing a living room in a typical house), the outdoor setting (OE) is more variable and less predictable, thus might demand greater processing effort. From our previous study in Azhari et al. (2018) that employed the same experimental paradigm, the OE context was found to elicit greater physiological arousal compared to the DE context. Similarly, we hypothesised that greater PFC activation will be observed when salient vocalisations are paired with the OE compared to the DE condition. Our finding supported this hypothesis: the left rostrolateral PFC, an area of the brain that facilitates relational integration, exhibited greater activation in the OE than DE condition which suggests that greater cognitive resources are required to process outdoor situational information together with salient vocalisations. The result from this study bears relevance in deepening our understanding of how contextual information differentially modulates the processing of salient vocalisations.